Swimming-induced changes in pulmonary function: special observations for clinical testing - Päivinen Marja; Keskinen Kari; Tikkanen Heikki (BMC, 2022)
Background
A special improvement in pulmonary function is found in swimmers. In clinical testing the airway reactivity is observed at certain exercise intensity and target ventilation. However, in highly trained swimmers exercising in water the reactions may not function the same way. The aim was to study the combined effects of the water environment and swimming on pulmonary function and the associations with perceived symptoms.
Methods
First, 412 competitive swimmers completed questionnaires concerning respiratory symptoms at different swimming intensities. Then, pulmonary function testing was performed in 14 healthy elite swimmers. Spirometry and maximal voluntary ventilation (MVV) were measured on land and in water before and after swimming. While swimming, minute ventilation (VE) tidal volume (VT) and breathing frequency (fb) were measured during competition speed swimming.
Results
Swimmers reported the most symptoms at competition speed intensity swimming. In the transition from the land into the water swimming body position, the ratio of forced expiratory volume in one second (FEV1) and forced expiratory capacity (FVC) (FEV1/FVC) decreased by a mean (SD) 5.3 % (3) in females and by 2.2 % (5) in males. During competition speed intensity swimming, the minute ventilation (VE) had a mean of 72 and 75 % of calculated maximal voluntary ventilation (cMVV) in females and in males, respectively.
Conclusions
Spirometry showed sex differences in water compared to land measurements. These differences should be considered when the effects of swimming are observed. During the intensity that triggered the symptoms the most, the VE was approximately 20 % higher than the target ventilations for clinical testing. These findings encourages specific modifications of clinical testing protocols for elite swimmers.